LEAFROLLERS (LEPIDOPTERA, TORTRICIDAE) OF AGROECOSYSTEMS OF THE FERGHANA VALLEY (Scientific journal of the Fergana State University, 2024)
The article describes the fauna of the leafrollers (Lepidoptera: Tortricidae) in the agroecosystems of the Fergana Valley. The leafrollers play a significant role in both natural and artificial communities of various zones of the Fergana Valley, and some of their representatives are pests in agroecosystems. As a result of the research, 4 species (Sparganothis pilleriana, Archips rosana, Pandemis cerasana, Aethes francillana) of the family Tortricidae were noted for the first time in the agroecosystems of the study area. According to the conclusion of preliminary studies, the number of leafrollers (Tortricidae) species that have a trophic relationship with the studied agrocenoses of the Fergana Valley is 23.